Data Mining Techniques and Trends - Gopalan, N. P; Sivaselvan, B (New Delhi PHI Learning, 2009)
This book describes the various phases of data mining, architecture of a data mining system, and the types of information that can be mined from databases
Includes bibliographical references and index
11
Keywords: Data Clustering; Data Mining; Multimedia Data Mining